The in vitro binding of Trypanosoma congolense to erythrocytes - Banks, K.L. (Wiley, 1979)
Synopsis.Trypanosoma congolense Broden, an intravascular parasite, binds to vessel walls and erythrocytes of infected hosts. In an attempt to characterize T. congolense adhesion to host cells, an in vitro assay was devised. It was shown in the in vitro experiments that T. congolense binds to bovine, sheep, and goat erythrocytes, but not always to erythrocytes of rats, mice, rabbits, horses or humans. Only the anterior part of live trypanosomes adheres to erythrocytes, and the attachment site on the trypanosomes is destroyed by trypsin and chymotrypsin. Trypanosomes did not adhere to bovine erythrocytes that had been incubated with neuraminidase, sodium periodate and poly‐L‐lysine. The foregoing experiments suggest that the surface of T. congolense contains a protein‐associated site which binds to sialic acid of some host cells. This surface site is most likely responsible for attachment to blood vessels in vivo.